2023
DOI: 10.1126/science.adi4107
|View full text |Cite
|
Sign up to set email alerts
|

Engineering ligand reactivity enables high-temperature operation of stable perovskite solar cells

Abstract: Perovskite solar cells (PSCs) consisting of interfacial two- and three-dimensional heterostructures that incorporate ammonium ligand intercalation have enabled rapid progress toward the goal of uniting performance with stability. However, as the field continues to seek ever-higher durability, additional tools that avoid progressive ligand intercalation are needed to minimize degradation at high temperatures. We used ammonium ligands that are nonreactive with the bulk of perovskites and investigated a library t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
57
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 141 publications
(72 citation statements)
references
References 69 publications
(74 reference statements)
2
57
0
Order By: Relevance
“…All of these factors cumulatively result in the total loss of device performance. Presently, numerous research efforts are being focused on addressing these issues through optimizing the absorber layer (crystal engineering and surface engineering), , employing a robust CTL , and a stable electrode design . The problems caused by external factors like moisture, oxygen, heat, and UV light can be properly mitigated by device encapsulation …”
Section: Introductionmentioning
confidence: 99%
“…All of these factors cumulatively result in the total loss of device performance. Presently, numerous research efforts are being focused on addressing these issues through optimizing the absorber layer (crystal engineering and surface engineering), , employing a robust CTL , and a stable electrode design . The problems caused by external factors like moisture, oxygen, heat, and UV light can be properly mitigated by device encapsulation …”
Section: Introductionmentioning
confidence: 99%
“…In recent years, perovskite solar cells (PSCs) based on organic–inorganic hybrid lead (Pb)-halide perovskite materials have been rapidly developed in the context of modern energy development. 1–4 Since 2009, its power conversion efficiency (PCE) has continued to soar from an initial 3.8% to 26.0%. 5–10 However, its commercial prospects have been limited due to the toxicity of Pb, resulting in the search for other environmentally friendly metal ions to replace Pb 2+ .…”
Section: Introductionmentioning
confidence: 99%
“…Most of these defects are concentrated on the grain boundaries or surface of perovskite crystals and can lead to deep-level traps such as coordination-deficient Sn 2+ , coordination-deficient halide ions (I − or Br − ), Sn clusters, and Sn-I translocation. 3–5,29,30 In addition, some point defects that can form shallow traps, such as I or MA/FA vacancies, may also occur during film growth. The presence of these defect states severely affects the optoelectronic properties of Sn-based perovskite films.…”
Section: Introductionmentioning
confidence: 99%
“…In the past few years, the wide energy gap of SnO 2 has been important to improve the device performance, which can be a good choice as ETL for optimizing PSCs. Recent research works have also demonstrated several benefits for SnO 2 , considering more efficient electron transport, enhanced energy band alignment to perovskites, and faster electron extraction as well as the involved interface of PSCs. Due to the promising properties of this material, recently, numerous efforts have been attempted to enhance the SnO 2 interface in the planar perovskite devices. …”
Section: Introductionmentioning
confidence: 99%